fs(1)h controls metabolic and immune function and enhances survival via AKT and FOXO in Drosophila - Sharrock,J; Estacio,Gomez A; Jacobson,J; Kierdorf,K; Southall,T; Dionne,M (Disease Models & Mechanisms, 2019)
The Drosophila fat body is the primary organ of energy storage as well as being responsible for the humoral response to infection. Its physiological function is of critical importance to the survival of the organism; however, many molecular regulators of its function remain ill-defined. Here, we show that the Drosophila melanogaster bromodomain-containing protein FS(1)H is required in the fat body for normal lifespan as well as metabolic and immune homeostasis. Flies lacking fat body fs(1)h exhibit short lifespan, increased expression of immune target genes, an inability to metabolize triglyceride, and low basal AKT activity, mostly resulting from systemic defects in insulin signalling. Removal of a single copy of the AKT-responsive transcription factor foxo normalises lifespan, metabolic function, uninduced immune gene expression and AKT activity. We suggest that the promotion of systemic insulin signalling activity is a key in vivo function of fat body fs(1)h.